Physics on the Fringe: Smoke Rings, Circlons, and Alternative Theories of Everything by Margaret Wertheim - Bauer, Henry (Journal of Scientific Exploration, 2012)
I don’t get it. I just don’t get it. This book is supposed to be about the relation between insider physics and outsider physics. It isn’t. As I read Physics on the Fringe, I was increasingly disappointed and frustrated at the amount of space given to Jim Carter, not only his “fringe physics” but also his personal doings. Admittedly he seems quite an interesting person, fun to be with, admirably self-motivated, helpful to others, a good citizen—not unlike quite a lot of other people. But his “circlon theory” isn’t an exemplar of fringe physics, it’s way-way-out pseudo-science. And Carter is not even typical of way-way-out crackpots: As Wertheim says, Carter atypically is a successful entrepreneur and has a sense of humor. So the book’s title misleads, and unfortunately the book’s substance also misleads about science and fringe science and pseudo-science in a number of ways.